Vulnerability, resilience, and rape: Uncovering the hidden work of police officers during rape investigations - Rumney, Phillip NS (International review of victimology, 2023)
Drawing on original empirical data comprising police interviews and case file analysis, this article seeks to better understand the policing responses to cases of rape and specifically, the ways in which officers assist victims in the context of two themes – encouraging engagement with the investigative process and ensuring victim safety and general welfare. This work – which we call ‘hidden work’ as it is often neglected in the research literature – involves victim care, multi-agency working, provision of practical assistance, along with efforts to protect victims from physical and psychological harm. This article reaffirms key observations in the existing literature that emphasise the importance of victim welfare and engagement as part of a police investigation. A focus on victim care can be seen as an end in itself but also as a strategy that may carry benefit to the police themselves in the pursuance of performance goals should a victim remain engaged with the criminal justice process. However, the central argument in this paper is that traditional measures of police performance, such as detection and arrest rates, miss a significant amount of police activity which are important to rape victims and that a broader range of considerations should be factored into discussion of police performance. This is suggested not to diminish or downplay the significance of traditional measures of performance, or indeed to minimise police shortcomings in these areas, but to facilitate a more nuanced discussion of some of the realities of investigative work in the complex field of sexual offences. The article concludes by arguing that much of this hidden work should be included in formal assessments of police performance alongside traditional key performance indicators.